ANALISIS YURISPRUDENSI PUTUSAN PENGADILAN AGAMA: GUGATAN PERCERAIAN KARENA TIDAK MEMILIKI KETURUNAN - Aziz, M. Abdul; Rahmawati, Rahmawati; Salma, Salma; Bakhtiar, Bakhtiar (FiTUA: Jurnal Studi Islam, 2024)
This study aims to analyze the sitting of the case and the judge's consideration and indication of the jurisprudence of religious court decisions regarding divorce due to the absence of children. The method used in this research is library research. Based on the analysis conducted, the judge in deciding this case paid attention to the formal and material requirements. For formal requirements, the judge considers that the divorce has fulfilled the elements stipulated in Government Regulation Number 9 of 1975 concerning the Implementation of the Marriage Law. In addition, judges consider the lawsuit or petition including witness testimony when determining material requirements. In considering their decision, the judges referred to relevant laws and regulations, Supreme Court jurisprudence, and applied legal istinrarbath by referring to the Qur'an, fiqh literature, and Dutch heritage laws such as R.Bg. and HIR. In four cases, there were three jurisprudences used by the judges, namely Supreme Court Jurisprudence Number 28PK.AG/1995 dated October 16, 1996, Supreme Court Jurisprudence Number: 379K/AG/1995 dated March 26, 1997, and Supreme Court Jurisprudence Number: 78K/AG/1999 dated October 20, 2000.